Recognition and killing of autologous, primary glioblastoma tumor cells by human cytomegalovirus pp65-specific cytotoxic T cells - Nair, Smita K; De Leon, Gabriel; Boczkowski, David; Schmittling, Robert; Xie, Weihua; Staats, Janet; Liu, Rebecca; Johnson, Laura A; Weinhold, Kent; Archer, Gary E; Sampson, John H; Mitchell, Duane A (Clinical cancer research, 2014)
Despite aggressive conventional therapy, glioblastoma (GBM) remains uniformly lethal. Immunotherapy, in which the immune system is harnessed to specifically attack malignant cells, offers a treatment option with less toxicity. The expression of cytomegalovirus (CMV) antigens in GBM presents a unique opportunity to target these viral proteins for tumor immunotherapy. Although the presence of CMV within malignant gliomas has been confirmed by several laboratories, its relevance as an immunologic target in GBM has yet to be established. The objective of this study was to explore whether T cells stimulated by CMV pp65 RNA-transfected dendritic cells (DC) target and eliminate autologous GBM tumor cells in an antigen-specific manner. T cells from patients with GBM were stimulated with autologous DCs pulsed with CMV pp65 RNA, and the function of the effector CMV pp65-specific T cells was measured. In this study, we demonstrate the ability to elicit CMV pp65-specific immune responses in vitro using RNA-pulsed autologous DCs generated from patients with newly diagnosed GBM. Importantly, CMV pp65-specific T cells lyse autologous, primary GBM tumor cells in an antigen-specific manner. Moreover, T cells expanded in vitro using DCs pulsed with total tumor RNA demonstrated a 10- to 20-fold expansion of CMV pp65-specific T cells as assessed by tetramer analysis and recognition and killing of CMV pp65-expressing target cells. These data collectively demonstrate that CMV-specific T cells can effectively target glioblastoma tumor cells for immunologic killing and support the rationale for the development of CMV-directed immunotherapy in patients with GBM.